Flugsanität in den abgelegen Teilen Sibiriens ; Mediziner verladen einen Patienten in einen Helikopter
soziale Fragen;Gesundheit;Gesundheitspolitik soziale Fragen;Gesundheit;Medizin soziale Fragen;Gesundheit;ärztlicher Beruf;Arzt/Ärztin soziale Fragen;Gesundheit;ärztlicher Beruf;arztähnlicher Beruf